2020
DOI: 10.1177/0706743720980080
|View full text |Cite
|
Sign up to set email alerts
|

Gambling and Problem Gambling in Canada in 2018: Prevalence and Changes Since 2002

Abstract: Objective: The purpose of this study was to provide an updated profile of gambling and problem gambling in Canada and to examine how the rates and pattern of participation compare to 2002. Method: An assessment of gambling and problem gambling was included in the 2018 Canadian Community Health Survey and administered to 24,982 individuals aged 15 and older. The present analyses selected for adults (18+). Results: A total of 66.2% of people reported engaging in some type of gambling in 2018, primarily lottery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 21 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…In Spain, lottery is one of the most traditional game mode with a relevant presence in the general population and within the clinical settings specialized in the treatment of behavioral addictions (Clotas et al, 2020). The prevalence rate in our work is consistent with other studies carried out in different countries, which have also reported a high percentage of people engaging in lottery and/or raffle tickets as their favorite gambling activity (Bhatia et al, 2019;Valleur, 2015;Williams et al, 2021). But it should be highlighted that the rates of gambling behavior/s worldwide evidence large variations across and within settings (Calado & Griffiths, 2016), and other studies have identified lottery gambling in a low proportion of treatment-seeking patients compared to alternative gambling forms (Ariyabuddhiphongs, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…In Spain, lottery is one of the most traditional game mode with a relevant presence in the general population and within the clinical settings specialized in the treatment of behavioral addictions (Clotas et al, 2020). The prevalence rate in our work is consistent with other studies carried out in different countries, which have also reported a high percentage of people engaging in lottery and/or raffle tickets as their favorite gambling activity (Bhatia et al, 2019;Valleur, 2015;Williams et al, 2021). But it should be highlighted that the rates of gambling behavior/s worldwide evidence large variations across and within settings (Calado & Griffiths, 2016), and other studies have identified lottery gambling in a low proportion of treatment-seeking patients compared to alternative gambling forms (Ariyabuddhiphongs, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Australia and Canada provide a useful point of comparison. They have similar socioeconomic and cultural characteristics, as well as similarities in policy frameworks (such as transitioning to public health policy models [ Productivity Commission, 2010 ]), and gambling behaviours, including problem gambling prevalence rates ( Armstrong & Carroll, 2017 ; Williams et al, 2021 ). However, they have different regulatory approaches to gambling and areas of research focus, as detailed in Baxter, Hilbrecht, and Wheaton (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…Over the last two decades, the number of people who gamble on the Internet has risen considerably. For example, in Canada, the prevalence of online gambling increased from 1.0 to 6.4% between 2002 and 2018 (Williams et al, 2021 ). In Australia, the prevalence of online gambling increased from 8.1 to 17.5% between 2010 and 2019 (Hing et al, 2021 as cited in Hing et al, 2022 ), and in Spain, overall online gambling expenditure quadrupled from 2.72 billion euros to 10.89 euros between 2012 and 2016 (Chóliz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%